Triphasic training: A high school strength & conditioning manual - Dietz, C. (CoachTube Inc., 2017)
This manual incorporates all of the training methods used with our athletes in an annual cycle. These training blocks provide each athlete with the qualities necessary to maximize performance. Successful athletic performances require the optimization of many qualities, including rate of force development, an aerobic base system, and of course max strength. Rate of force development is vital in athletics. During maximal velocity contractions, as seen in competition, there is not enough time for maximal muscular force to be reached. This means athletes must have the goal of producing the most force possible in the time allowed during competition. The aerobic base is improved through the proper use of conditioning methods throughout the year. Adaptations to this system are vital for recovery in repeat-effort sports, which includes all team sports. Maximal strength is the most common method of training used and does have its place in improving performance, however, it is important to realize improvements in this quality do not always transfer to sport`s success.